Exact null internal controllability for the heat equation on unbounded convex domains∗. (6th February 2014) - Barbu, Viorel
Abstract : The liner parabolic equationyt-12 y+F· a y=1__0u ∂y ∂t − 1 2 Δy + F · ∇ y = 1 𝒪 0 u with Neumann boundary condition on a convex open domain 𝒪 ⊂ ℝ d with smooth boundary is exactly null controllable on each finite interval if 𝒪0 is an open subset of 𝒪 which contains a suitable neighbourhood of the recession cone of 𝒪 . Here, F : ℝ d → ℝ d is a bounded, C 1 -continuous function, and F = ∇ g, where g is convex and coercive.